An avenue for replacement of chemical fertilization under rice-rice cropping pattern: Sustaining soil health and organic C pool via MSW-based vermicomposts. Issue 10 (23rd August 2020) - Sahariah, Banashree; Das, Subhasish; Goswami, Linee; Paul, Sarmistha; Bhattacharyya, Pradip; Bhattacharya, Satya Sundar
ABSTRACT: The impacts of Municipal solid wastes (MSW) vermicompost (VC) on soil-crop interface have rarely been studied. Hence, the influence of vermicompost on soil health and soil organic C (SOC) dynamics was assessed under intensive rice–rice cropping system. A 20–40% of the recommended N-fertilization was substituted by MSW-vermicompost for the crop. SOC storage, degree of humification, humic acid C, and fulvic acid C in soil gradually increased by 55–60% under NPK60  + VC and NPK80  + VC treatments in 2 years. The improvement in N-mineralization was spectacular in NPK60  + VC (2.79 folds) and NPK80  + VC (2.25 folds) treated soil. The carbon pool management index in soil was greatest under NPK60  + VC (2.1) treatment followed by NPK100  + VC (1.96) and NPK80  + VC (1.87) treatments. Moreover, the crop biomass and grain yield increased under VC treatments. The correlation and regression statistics revealed that rice production was enhanced due to improvement of SOC pool and humified carbon fractions in soil. Finally, we recorded highest benefit-cost ratio under NPK60  + VC (benefit/cost 5.55) followed by NPK80  + VC (benefit/cost 5.44). The study indicated that MSW-vermicompost sustained soil microbial health and SOC balance, which significantly correlated with rice production.